DEVELOPING TEACHING MEDIA OF KANGAROO SMART FRIEZE TO ENRICH ELEMENTARY SCHOOL STUDENTS’ VOCABULARY (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2015)
The implementation of the newest curriculum (Curriculum 2013) leads some elementary schools to finally exclude English from the schools subjects. However, some elementary schools that keep teaching English as a subject still cannot provide appropriate English teaching media, especially to teach vocabulary. In this study, the researcher aimed to know the problems faced by the English teacher and the fourth grade students of SD N 2 Sekaran in the vocabulary teaching and learning, and also to know how to develop teaching media of Kangaroo Smart Frieze. The Research and Development (R & D) approach was adopted by conducting the preliminary survey, designing and developing the prototype of the product, conducting limited testing and product validation, having a revision process and describing the research result. The subjects of the study were the fourth grade students of SD N 2 Sekaran in the academic year of 2013/2014. The instruments used were questionnaires, interview guideline and test. According to the interview to the English teacher and students, it can be concluded that the vocabulary teaching media Kangaroo Smart frieze needs to be developed with the focus on the quality of the media and also the variety of games played. The development of Kangaroo Smart Frieze was started by observing and interviewing the English teacher and students. After doing that, the process was continued by planning the data collecting instrument of vocabulary teaching media. The main consideration was based on the English curriculum (syllabus) of the fourth grade students of elementary school and also some related theories. Moreover, the data collecting instrument was arranged into two main parts which included the need analysis of the students and English teacher. The further step was designing the prototype. The development process was then followed by other steps; product validation, try-out (limited testing) and revision of Kangaroo Smart Frieze. The results of the students’ test by using Kangaroo Smart Frieze as the vocabulary teaching media, and also the assessment from the experts were very good. Therefore, it could be concluded that Kangaroo Smart Frieze has a good prospect to be used in the vocabulary teaching and learning process. As suggestion, the teachers should always try to choose appropriate vocabulary teaching media, and the future researchers should conduct better research and development to develop better vocabulary teaching media for elementary school students.